RF-frontend design for process-variation-tolerant receivers - Sakian, Pooyan (Analog Circuits and Signal Processing, 2012)
This book discusses a number of challenges faced by designers of wireless receivers, given complications caused by the shrinking of electronic and mobile devices circuitry into ever-smaller sizes and the resulting complications on the manufacturability, production yield, and the end price of the products.  The authors describe the impact of process technology on the performance of the end product and equip RF designers with countermeasures to cope with such problems.  The mechanisms by which these problems arise are analyzed in detail and novel solutions are provided, including design guidelines for receivers with robustness to process variations and details of circuit blocks that obtain the required performance level. Describes RF receiver frontends and their building blocks from a system- and circuit-level perspective; Provides system-level analysis of a generic RF receiver frontend with robustness to process variations; Includes details of CMOS circuit design at 60GHz and reconfigurable circuits at 60GHz; Covers millimeter-wave circuit design with robustness to process variations.